1999
DOI: 10.1007/bf02461353
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physiological roles of neurotransmitters during individual development

Abstract: The classical neurotransmitters (acetylcholine and biogenic monoamines) are multifunctional substances involved in intra- and intercellular signaling at all stages of ontogenesis in multicellular animals. A cyclical scheme is proposed to describe age-related changes in neurotransmitter functions at different stages of development from oocyte maturation to neuron formation. This may reflect not only the temporospatial organization of neurotransmitter processes, but also the origin of the functions of acetylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…165,167 To date, it has been reported that oocytes of starfish, fish, amphibians, and mammals contain 5-HT, and 5-HT receptors have been detected on the cell surface of oocytes as well as follicular cells of various species. 168 Even prior to the presence of differentiated serotonergic neurons releasing neurotransmitter, 5-HT is involved in the regulation of basic developmental processes related to early embryogenesis, including cell proliferation, migration, differentiation, and morphogenetic cell movements during gastrulation and postgastrulation. 165 By controlling morphogenesis, for instance, 5-HT of maternal origin appears to influence the development and maturation of the mouse brain.…”
Section: Serotonergic Regulation Of Embryo Developmentmentioning
confidence: 99%
“…165,167 To date, it has been reported that oocytes of starfish, fish, amphibians, and mammals contain 5-HT, and 5-HT receptors have been detected on the cell surface of oocytes as well as follicular cells of various species. 168 Even prior to the presence of differentiated serotonergic neurons releasing neurotransmitter, 5-HT is involved in the regulation of basic developmental processes related to early embryogenesis, including cell proliferation, migration, differentiation, and morphogenetic cell movements during gastrulation and postgastrulation. 165 By controlling morphogenesis, for instance, 5-HT of maternal origin appears to influence the development and maturation of the mouse brain.…”
Section: Serotonergic Regulation Of Embryo Developmentmentioning
confidence: 99%
“…In particular, studies of the functional linkage of such systems with various second messengers were very relevant [3,5,10,22,34]. One of these studies [4] showed that acetylcholine increases the level of specific anomalies arising as a result of exposure of early sea urchin embryos to protein kinase C activators.…”
mentioning
confidence: 99%
“…We hypothesize that neurotransmitters could mediate the homotypic inhibitory signaling implied by our results. Several attributes of neurotransmitters and their signaling mechanisms make them attractive candidates: they provide a basis for cell-type specificity; plausible mechanisms for neurotransmitter delivery have been reported, including volume transmission of molecules released from a synaptic apparatus (Mora-Ferrer et al, 1999;Cragg and Rice, 2004); neurotransmitters can activate complex intracellular signaling cascades, potentially resulting in changes in gene transcription (Paspalas and Goldman-Rakic, 2004); neurotransmitters are known to regulate various aspects of cellular development (Lankford et al, 1988;Rodrigues et al, 1990;Jung and Bennett, 1996;Lima et al, 1996;Buznikov et al, 1999;Moiseiwitsch, 2000;Zachor et al, 2000;Herlenius and Lagercrantz, 2001). Direct evaluation of the neurotransmitter hypothesis of cell-fate determination and cellular pattern formation in the growing goldfish retina is the subject of ongoing investigation.…”
Section: Hypothesized Signaling Mechanisms For Controlling Cell-fate mentioning
confidence: 99%